Arrival of rabbit haemorrhagic disease virus 2 to northern Europe: Emergence and outbreaks in wild and domestic rabbits (Oryctolagus cuniculus) in Sweden. Issue 1 (13th April 2017) - Neimanis, A. S.; Ahola, H.; Zohari, S.; Larsson Pettersson, U.; Bröjer, C.; Capucci, L.; Gavier‐Widén, D.
Summary: Incursion of rabbit haemorrhagic disease virus (RHDV) into Sweden was documented in 1990 and it is now considered endemic in wild rabbit ( Oryctolagus cuniculus ) populations. Rabbit haemorrhagic disease virus 2 (RHDV2), a new, related lagovirus was first detected in France in 2010, and has spread rapidly throughout Europe and beyond. However, knowledge of RHDV2 in northern Europe is sporadic and incomplete, and in Sweden, routinely available diagnostic methods to detect rabbit haemorrhagic disease (RHD) do not distinguish between types of virus causing disease. Using RHDV2‐specific RT‐qPCR, sequencing of the VP60 gene and immunological virus typing of archived and prospective case material from the National Veterinary Institute's (SVA) wildlife disease surveillance programme and diagnostic pathology service, we describe the emergence of RHDV2 in Sweden in both wild and domestic rabbits. The earliest documented outbreak occurred on 22 May 2013, and from May 2013 to May 2016, 10 separate incidents of RHDV2 were documented from six different municipalities in the southern half of Sweden. Phylogenetic analysis of the VP60 gene shows clear clustering of Swedish isolates into three separate clusters within two different clades according to geographic location and time, suggesting viral evolution, multiple introduction events or both. Almost all cases of RHD examined by SVA from May 2013 to May 2016 were caused by RHDV2, suggesting that RHDV2 may be replacing RHDV as the predominant cause of RHD in Sweden.